Skinning Injury Responses in Sweetpotato - Jollanda Effendy; Don R LaBonte; Darda Efendi; Nurul Khumaida; Gustaaf A Wattimena (JURNAL BUDIDAYA PERTANIAN, 2021)
In sweetpotatoes (Ipomoea batatas L. Lamb), the loss of skin from the surface of the storage roots is known as skinning injury. It is responsible for significant postharvest loss resulting from moisture increase and weight reduction, wrinkling, and susceptibility to pathogen attack. Reduced root weight by water loss is associated with a higher rate of rot predominantly occurred in the developing and underdeveloped countries which can count of 8-20% of postharvest loss. Plants have different adaptation to protect themselves against skinning injury. Lignification, suberization, and increased sugar at the wound site have been shown to be correlated with wound healing. Changing in gene expressions have been associated with skinning injury. Genes associated in the biosynthesis of lignin and suberin, protein fate, cell-wall modification, transcription and protein synthesis, and stress responses and defense have been associated with skinning injury responses in plants. Understanding the skinning injury responses and how to regulate them can be used to produce a more desirable plant resistant to skinning injury. This paper especially reviews and discusses skinning injury responses in sweetpotato, a root crop which product may severely be affected by skinning injury. Keywords: gene expression, Ipomoea batatas, lignification, postharvest loss, wounding ABSTRAK Pada ubi jalar (Ipomoea batatas L. Lamb), cedera kulit adalah hilangnya kulit dari permukaan umbi. Cedera kulit ini bertanggung jawab atas kerugian pascapanen yang signifikan akibat peningkatan laju kelembaban dan penurunan berat umbi, pengerutan, dan kerentanan terhadap serangan patogen. Berat umbi yang berkurang karena kehilangan air dikaitkan dengan tingkat pembusukan yang lebih tinggi, terutama terjadi di negara-negara berkembang dan yang kurang berkembang dengan kehilangan hasil panen umbi 8-20%. Tanaman memiliki adaptasi yang berbeda untuk melindungi diri dari cedera kulit. Lignifikasi, suberisasi, dan peningkatan gula di lokasi pelukaan telah terbukti berkorelasi dengan penyembuhan luka. Perubahan ekspresi gen telah dikaitkan dengan cedera kulit. Gen-gen yang terlibat dalam jalur biosintesis lignin dan suberin, protein tujuan akhir, modifikasi dinding sel, transkripsi dan sintesis protein, serta respons stres dan pertahanan telah dikaitkan dengan respons cedera kulit pada tanaman. Memahami respons cedera kulit dan bagimana cara mengaturnya dapat digunakan untuk menghasilkan tanaman yang diinginkan yang tahan terhadap cedera kulit umbi. Paper ini secara khusus mengulas dan membahas respon cedera kulit pada ubi jalar, suatu tanaman umbian yang hasilnya sangat terpengaruh oleh cedera kulit. Kata kunci: ekspresi gen, Ipomoea batatas, lignifikasi, kehilangan pascapanen, pelukaan